Processing of Magnesium Porous Structures by Infiltration Casting for Biomedical Applications1. Issue 2 (9th October 2013) - Trinidad, Javier; Marco, Iñigo; Arruebarrena, Gurutze; Wendt, Joachim; Letzig, Dietmar; Sáenz de Argandoña, Eneko; Goodall, Russell
Abstract Magnesium and its alloys are currently considered to be a promising metallic biomaterial. The interest in magnesium alloys arises from their biocompatibility, bioabsorbility, and especially from their mechanical properties, which are more compatible to those of human bone than the mechanical properties of other metallic biomaterials, such as stainless steel and titanium. A medical application in which magnesium is gaining interest is regenerative medicine where scaffolds are used to create tissues from cells. For its application in regenerative medicine, the scaffolds have to present a 3D open‐cell structure. The main purpose of the present research is to set up the fabrication procedure necessary to manufacture porous magnesium scaffolds; for this the replication (infiltration) process has been used and adapted to process magnesium alloys, processing five different biodegradable magnesium alloys (AZ91E, WE43, ZM20, ZWM200, and ZXM200).